KEBIJAKAN PENDANAAN, INSIDER OWNERSHIP DAN FIRM SIZE TERHADAP NILAI PERUSAHAAN YANG LISTED DI BURSA EFEK INDONESIA (BEI) TAHUN 2010-2013 - Supriyanah .; Nunung Ghoniyah (Jurnal Ekonomi dan Bisnis, 2015)
This research is conducted for testing the influence of debt to equity ratio, insider ownership and firm size to price book value with the dividend payout ratio as the intervening variable in the firms registered at Indonesian Capital Market in the period of 2010 through 2013.Sampling technique applied in this research is purposive sampling. The data are collected based on the publication of Indonesian Capital Market Directory and www.idx.co.id. A number of 36 sample companies out of 472 companies registered at Indonesian Capital Market are obtained. Analytictechnique applied in this research is double linier regression to obtain a thorough picture ofthe relation between one variable and the others. This research is measured by seeing the determination coefficient, statistic value of F, statistic value of t, and intervening test. Besides, classic assumption test is also conducted, involving normality, multicollinearity, auto-correlation,and heteroscedasticity tests.The analysis result shows that DER variable partially influences significantly negative to DPR, insider ownership variable partially influences significantly positive to DPR, firm size variable partially influences significantly positive to DPR, DER variable partially influences significantly negative to PBV, insider ownership variable influencessignificantly positive to PBV, firm size variable partially influences significantly positive to PBV and DPR variable partially influences significantly positive to PBV. The regression test result with intervening variable states that Dividend Policy (DPR) is not intervening variable, Debt to Equity Ratio (DER) variable, insider ownership and firm size toward Price Book Value (PBV).Keywords: Debt to Equity Ratio, insider ownership, firm size, dividend payout ratio and price book value